1999
DOI: 10.1902/jop.1999.70.8.869
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postsurgical Naproxen and a Bioabsorbable Membrane on Osseous Healing in Intrabony Defects

Abstract: The administration of postsurgical naproxen failed to produce osseous healing that was statistically superior to that obtained with polylactide bioabsorbable membranes alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Lane et al (1990) reported that naproxen slowed bone formation in ovariectomized rats. Bichara et al (1999) showed that the post-surgical use of naproxen failed to produce osseous healing, which is in agreement with the present study. In earlier studies it was stated that the weakening effect of naproxen on fracture healing reduces the synthesis of prostaglandin by inhibiting the cyclooxygenase enzyme (Reuben and Connelly, 2000;Lipsky, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Lane et al (1990) reported that naproxen slowed bone formation in ovariectomized rats. Bichara et al (1999) showed that the post-surgical use of naproxen failed to produce osseous healing, which is in agreement with the present study. In earlier studies it was stated that the weakening effect of naproxen on fracture healing reduces the synthesis of prostaglandin by inhibiting the cyclooxygenase enzyme (Reuben and Connelly, 2000;Lipsky, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Many factors, such as the use of NSAIDs for the prevention of bone fracture pain, can affect this process. Recent studies have shown that these drugs affect the process of bone fracture healing [29][30][31]. NSAIDs interfere with the arachidonic acid mechanism by blocking the formation of PGs through the inhibition of the cyclooxygenase pathway, which plays a fundamental role in the bone healing process [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…GBR is an accepted surgical method used in implant dentistry to increase the quantity and quality of host bone in areas of localized alveolar defects 26‐32 . When a GBR technique is used, it is suggested that implant treatment can be performed in patients with insufficient bone width or lack of a suitable bone donor site 33‐35 …”
Section: Discussionmentioning
confidence: 99%